Stigma Terhadap Guru Muslim di Sekolah Katolik - Deni Aries Kurniawan; Daniel Theodore Sparringa; Tuti Budirahayu (Journal of Urban Sociology, 2023)
AbstractThis study aims to explore the stigma received by Muslims who work in Catholic schools and the stigma management carried out by the subject for stigmatization and at the same time as an effort to reduce the social tension that arises. Departing from an interpretive paradigm, this study explores four subjects who work as teachers in a Catholic school in the city of Surabaya. This study uses in-depth interviews for data collection techniques. This study finds that being a teacher in a Catholic school is a story about fighting against the notion of 'deviance'; 'strange'; as well as 'taboo' in the midst of a multicultural society. Therefore, identity as a teacher in a Catholic school has led to a response that ends in stigma within each subject. The stigma comes from the closest environment, namely the spouse's relatives and peers who are fellow Muslims. These forms of stigma include being considered deviant, sarcasm, and being labeled as infidel. Meanwhile, stigma management , which is carried out as an effort to manage stigma and reduce tension, is to clarify, make the stigma a source of humor, and hide the stigmatized identity. This study also found a new concept called 'manoritas'.Keywords : Identity; Manoritas; Stigma; Stigma Management